2012
DOI: 10.1007/s13760-012-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of cinnarizine in the prophylaxis of migraine headaches in children: an open, randomized comparative trial with propranolol

Abstract: Migraine headaches are common in children. Early diagnosis and appropriate interventions are mandatory to prevent decades of suffering and diminished quality of life. There is need for data regarding the efficacy and safety of prophylactic agents in children with migraine; therefore, we designed a randomized clinical trial to compare the efficacy and safety of cinnarizine with that of a well-known prophylactic agent (propranolol) in the prophylaxis of pediatric migraine headache. A total of 120 patients aged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…Both showed a significant reduction in headache frequency with either drug, and there was no significant difference between propranolol and valproate. An open, randomized comparison of propranolol and cinnarizine showed equal efficacy in reduction of headache frequency, although cinnarizine is not available in the United States or Canada. Although these studies suggest that propranolol is effective in pediatric migraine, none of the above studies had a placebo control, which limits interpretation of the results.…”
Section: Antihypertensivesmentioning
confidence: 98%
See 2 more Smart Citations
“…Both showed a significant reduction in headache frequency with either drug, and there was no significant difference between propranolol and valproate. An open, randomized comparison of propranolol and cinnarizine showed equal efficacy in reduction of headache frequency, although cinnarizine is not available in the United States or Canada. Although these studies suggest that propranolol is effective in pediatric migraine, none of the above studies had a placebo control, which limits interpretation of the results.…”
Section: Antihypertensivesmentioning
confidence: 98%
“…As noted above, cinnarizine has limited evidence for use in pediatric migraine. However, one open label, randomized trial comparing cinnarizine and propranolol in pediatric migraine showed similar reduction in headache frequency with either medication …”
Section: Antihypertensivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Широко применяются в клинической практике с превентивной целью и блокаторы кальциевых каналов (флунаризин, циннаризин). В исследованиях при сравнении циннаризина с бета-блокатором (пропрано-лол) и антиконвульсантом (вальпроат) циннаризин про-демонстрировал сходную профилактическую эффектив-ность и переносимость [46,47].…”
Section: применение фезама при мигрениunclassified
“…All four demonstrated efficacy and safety parameters in line with previous studies, even in lower doses (0.5 to 1 mg/ kg). 55,56,60,61 Propranolol must not be prescribed to patients with a history of atopic disease, asthma, diabetes, or heart block. Moreover, the authors do not administer propranolol to athletic patients because it may interfere with their physical activity.…”
Section: Antihypertensivesmentioning
confidence: 99%